Optimization strategy for planing hull design - Thai Gia Tran; Quang Van Huynh; Hyun Cheol Kim (International Journal of Naval Architecture and Ocean Engineering, 2022)
The planing hull optimization has always been a difficult problem due to the trim changes caused by lift force and complex hydrodynamic interactions at high speeds. In this paper, a strategy is presented to optimize a planing hull design, starting from using dimensional analysis to establish a resistance objective function depending on three dimensionless hull form parameters, then using CFD or Savitsky method to predict resistance for each hull variant formed by changing each pair of hull form parameters in the resistance objective function, and finally, determining an optimal hull form variant with minimum resistance based on the combination of the Kriging surrogate model and Neldel-Mead optimization algorithm. In addition, our modified Savitsky computational procedure and suitable inputs for the CFD solver are also applied to improve the accuracy of planing hull resistance predictions. For practicality, the proposed strategy was applied to evaluate the design of a high-speed vessel, named K88, which was model tested but did not achieve the expected performance. As a result, this vessel can be optimally redesigned with the ability to reduce total resistance by about 11.3% when simultaneously correcting deadrise angle and breadth, and by about 19.4% when simultaneously correcting deadrise angle and chine height at the bow.